School quality and staying-on in Northern Ireland: resources, peer groups and ethos - McVicar, Duncan (Economic & Social Studies, 2001)
The paper examines career choice at age 16 in Northern Ireland using micro data for young people completing compulsory education in 1993. Explanatory variables include resource related school characteristics, ethos-related characteristics and peer-group factors. The results suggest resources, ethos and peer group effects all play a significant role in career choice at age 16. Some of these factors, including pupil/teacher ratios, act in opposite directions on the probability of entry into Further Education College and of staying-on at school, suggesting studies of school quality on choice at age 16 should disaggregate post-compulsory education where possible.
Keywords: Career choice; School quality; Northern Ireland; Further education; School pupils